Whistleblowing intention: Gen Z as whistleblower - Arismaya, Anisa Dewi (Journal of Contemporary Accounting, 2025)
Indonesia is one of the countries with a high rate of fraud, one of which is corruption. Corruption needs to be eradicated because it is detrimental to the state and organizational culture. Efforts to prevent corruption need to be carried out not only from the external organization but also from within the organization because internal parties should know how the organization's condition is running, one of which is through whistleblowing. Whistleblowing is one of the media for disclosing unethical behavior in organizations that can be done by employees, leaders, and the community. The purpose of this study is to find out the factors that affect whistleblowing intentions with quantitative research methods. The sampling technique used was saturated sampling, namely 172 students of the Auditing course of the Faculty of Islamic Economics and Business UIN Salatiga. The data collection method uses a survey technique, namely a questionnaire. The hypothesis of this study is that personal cost has a negative effect on the intention to whistleblow, the level of seriousness of the fraud has a positive effect on the intention to whistleblow, the organization's commitment has a positive effect on the intention to whistleblow, and professionalism has a positive effect on the intention to whistleblow.